FROM THE HISTORY OF ARCHAEOLOGICAL CONGRESSES IN UKRAINE - Пеняк, Павло (SWorldJournal, 2025)
Some aspects of activity of Archaeological congresses, which were founded by Archaeological society in Moscow and its head count Uwarow are analyzed at the article. Short characteristic of all 15 archaeological congresses is given. General problems to whi